A pilot study of thiamin and folic acid in hemodialysis patients with cognitive impairment. Issue 1 (1st January 2021) - Lu, Renhua; Fang, Yan; Zhou, Yijun; Che, Miaolin; Shen, Jianxiao; Liu, Qian; Zhang, Haifen; Pan, Shuting; Lin, Yan; Wang, Qin; Mou, Shan; Ni, Zhaohui; et al.
Abstract: Objective: This study aimed to explore the effectiveness of thiamin and folic acid supplementation on the improvement of the cognitive function in patients with maintenance hemodialysis. Method: In the present study, we randomly assigned patients undergoing hemodialysis who had the Montreal Cognitive Assessment (MoCA) score lower than 26 to treatment group ( n = 25, thiamin 90 mg/day combined with folic acid 30 mg/day) or control group ( n = 25, nonintervention). All subjects were followed up for 96 weeks. The primary outcome was the improvement of the MoCA score. The secondary outcomes included homocysteine level, survival and safety. Results: Patients in treatment group had an increase of the MoCA score from 21.95 ± 3.81 at baseline to 25.68 ± 1.96 at week 96 ( p < 0.001, primary outcome), as compared with the MoCA score from 20.69 ± 3.40 to 19.62 ± 3.58 in control group. Thiamin combined with folic acid treatment also resulted in lower level of serum homocysteine in treatment group compare with control group at week 96 ( p < 0.05, secondary outcome). 3 patients and 9 patients died during follow-up period in treatment and control group respectively ( p = 0.048). The proportion of adverse events in treatment group was significantly lower than that in control group. Conclusion: Hemodialysis patients with cognitive impairment treated with thiamin and folic acid had a significant improvement in MoCA score.